Pandangan Guru Akidah Akhlak terhadap Pelaksanaan Pendidikan Akhlak melalui Pembelajaran Kitab Ta’lim al-Muta’allim sebagai Strategi Pencegahan Bullying di MTs Islamiyah Syafiiyah Sedan - Syafi’ul Amin; Siti Inayatul Umaroh; Ana Achoita (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the perspectives of Akidah Akhlak teachers on the implementation of moral education through the teaching of the Ta’lim al-Muta’allim book as a strategy to prevent bullying at MTs Islamiyah Syafiiyah Sedan. The background of the study is the growing prevalence of bullying in schools, including verbal, physical, and social forms, which demands an approach to moral education that not only transfers knowledge but also internalizes values essential for shaping students’ character and self-control. This research employs a descriptive qualitative method using interviews, observations, and documentation. The research subjects are Akidah Akhlak teachers who directly teach Ta’lim al-Muta’allim. The data were analyzed through reduction, display, and conclusion drawing. The findings show that teachers view the book as strategically valuable for developing students’ moral character because it provides guidance on proper conduct toward teachers, peers, knowledge, and the learning environment. According to the teachers, applying the values presented in the text helps foster respect, empathy, and social responsibility, which contributes to preventing bullying behaviors. In classroom practice, teachers integrate these values through exemplary behavior, contextual advice, and reflective discussions following reading activities. Thus, the teaching of Ta’lim al-Muta’allim serves not only as academic material but also as a medium for instilling moral values that support the creation of a school culture grounded in good morals and free from bullying. These efforts strengthen students’ awareness and encourage positive daily interactions within the school.